Traffy Fondue: a smart city citizen engagement - Hansen, Michael Motet; Dahiya, Bharat (Frontiers in Sustainable Cities, 2025)
As urban areas seek innovative solutions to enhance quality of life, integrating citizen participation in smart city projects has become increasingly important. Traditionally viewed as top-down initiatives, these projects can substantially benefit from incorporating citizen feedback and active involvement in addressing urban challenges effectively. This research addresses how citizen participation can enhance the success of smart city projects. Specifically, it explores the case of Traffy Fondue in Bangkok, a digital platform designed to facilitate citizen engagement in officially reporting and resolving urban issues. The study employed a mixed-methods approach, including analyzing data collected from the Traffy Fondue platform and semi-structured stakeholder interviews. The interviews provided insights into stakeholders' perceptions of success factors, while the data analysis focused on identifying common urban challenges and the platform's effectiveness in addressing them. The results indicate that citizen participation, facilitated through the Traffy Fondue platform, significantly contributes to the success of smart city projects. The platform enabled comprehensive data collection on urban issues, allowing for effective problem-solving and enhanced city operations. Stakeholders highlighted the importance of feedback mechanisms and the role of citizen engagement in achieving successful outcomes. Traffy Fondue demonstrated an 84% citizen satisfaction rate while generating annual cost savings of US$2.14 million for the public sector. The study highlights that incorporating citizen feedback improves the resolution of urban challenges while fostering community engagement and trust in city governance.